2018
DOI: 10.1016/j.tourman.2017.10.009
|View full text |Cite|
|
Sign up to set email alerts
|

Does a happy destination bring you happiness? Evidence from Swiss inbound tourism

Abstract: This study aims to explain tourist happiness by examining a specific destination in which happiness is generated for tourists via their travel behavior at the destination. Building upon the spillover theory of happiness, we developed a destination-based model of tourist happiness, which is shaped by destination image and service quality and mediated by tourist satisfaction and life satisfaction. This model was tested using data from 1,048 inbound tourists in Switzerland in 2015. We found that destination image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 85 publications
1
76
0
6
Order By: Relevance
“…At the second level, branches appear that leave each of the nodes and are organized hierarchically. Finally, as mentioned above, a series of indicators are obtained that reflect each of the categories related to the object of study [43,44].…”
Section: Textual Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…At the second level, branches appear that leave each of the nodes and are organized hierarchically. Finally, as mentioned above, a series of indicators are obtained that reflect each of the categories related to the object of study [43,44].…”
Section: Textual Analysismentioning
confidence: 99%
“…Using the Tourist Happiness Index, Chen and Li [44] analyzed the positive feeling of the tourists who stayed in Swiss hotels of environmental tourism. Furthermore, Abou-Zeid et al [61] concluded [62][63][64][65].…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%
“…Recent research has found that negative emotions and stereotypes will remain unchanged in the travel experience, which negatively affects destination image [33]. By using life satisfaction, eudemonia, and affect as the explanatory variables to measure tourists' happiness, Chen concluded that positive emotions change more than negative affect towards the destination image [34].…”
Section: Museums and Destination Imagementioning
confidence: 99%
“…The individual attributes of tourists, the characteristics of the tourist generating region, destination features, and other environmental factors significantly impact the unbalanced distribution of tourist flow [23][24][25] in both the time and spatial dimensions. On the tourism supply side, the importance of the destination market's "demand to undertake" is self-evident [26]. The full development of the supply side of the destination market is one of the important aspects to achieve a balanced development of the inbound tourism industry in China [27].…”
Section: Literature Reviewmentioning
confidence: 99%